Genomic comparisons of carbonic anhydrase V genes in vertebrates - Vyakkereva, Elvira (fi=Turun yliopisto|en=University of Turku|, 2018)
Carbonic anhydrases are involved in many processes of life, have been discovered in every living organism, and are widely distributed in tissues. Carbonic anhydrases are involved in different biochemical processes, such as respiration, calcification, gluconeogenesis, regulations of pH in pancreatic juice and saliva, vision, formation of cerebrospinal fluid, gustation, olfaction, etc. Carbonic anhydrase deficiency is often a direct or indirect cause of certain diseases, such as obesity. The previous research also suggests that it can be assumed that both enzymes play a role in ammonia detoxification and regulate blood sugar level. This makes them attractive for the researchers. The goal of this work was to study CA VA and CA VB genes in vertebrates, to compare them, and to find their differences and similarities. The genes have a high similarity between each other, but they have different rates of evolutionary development. Comparative genomic DNA sequence-based analysis, genomic browsers, other various bioinformatic methods and tools were used in this study in oder to analyse the carbonic anhydrase V genes.